Effect of take-off angle on start performance in swim-start - Takeda, T.; Ichikawa, H.; Tsubakimoto, S.; Nomura, T. (1st International Scientific Conference of Aquatic Space Activities, 2008)
The purpose of this study was to clarify the effect of the take-off angle change on the take-off velocity, flight distance and time on the starting block, and suggest the appropriate take-off angle range for the start performance until water entry. Twelve well trained male swimmer participated as a subject in this study. Each subject performed the grab start from the starting block with the three different take-off angles (Higher: HT, Normal: NT, Lower: LT). Kinematic variables were calculated by 2D motion analysis using the DLT method. There was significant correlation between the body angle at the take-off and the take-off velocity. The decrement of take-off angle resulted in the significant increment of take-off velocity, significant decrement of flight distance, and no significant difference of block time. Proper take-off angle range for the start performance until water entry was from 11.8deg to -18.7deg.